Molecular basis of rootstock-related tolerance to water deficit in Vitis vinifera L. cv. Sangiovese: A physiological and metabolomic combined approach. (October 2020) - Lucini, Luigi; Miras-Moreno, Begona; Busconi, Matteo; Marocco, Adriano; Gatti, Matteo; Poni, Stefano
Highlights: M4 grafting improved Sangiovese grapevine resistance to water stress. M4 was able to deliver similar CO2 at a significantly reduced water use. Cytokinins and gibberellins distinctively accumulated in M4 grafted vines under drought. A reduced accumulation of ROS in M4 grafted vines can be postulated. Abstract: The rootstock M4 ( V. vinifera × V. berlandieri ) × V. berlandieri cv. Resseguier n.1) is a recent selection reported to confer improved drought tolerance to grafted V. vinifera scions, a very desired feature in the era of global warming. Therefore, a short-term study was performed on a batch of 12 potted cv. Sangiovese vines grafted either on M4 or on the drought susceptible SO4 rootstock. Ecophysiological assessments as whole canopy net CO2 exchange rate (NCER), transpiration (Tc ), and pre-dawn leaf water potential (Ψpd ) and UHPLC-ESI/QTOF-MS metabolomics were then used to investigate the different vine responses during water limiting conditions. Water stress was induced by applying 50 % of estimated daily water use from days of year 184–208. M4 was able to deliver similar CO2, at a significantly reduced water use, compared to SO4 grafting. In turn, this resulted in enhanced canopy water use efficiency (NCER/Tc ratio) quantified as +15.1 % during water stress and +21.7 % at re-watering. Untargeted metabolomics showed a similar modulation of brassinosteroids and ABA between the two rootstocks, whereas the up accumulation of cytokinins and gibberellins under drought was peculiar of M4 grafted vines. The increase in gibberellins, together with a concurrent down accumulation of chlorophyll precursors and catabolites and an up accumulation of folates in M4 rootstock suggests that the capacity of limiting reactive-oxygen-species and redox imbalance under drought stress was improved. Finally, distinctive osmolyte accumulation patterns could be observed, with SO4 investing more on proline and glycine-betaine content and M4 primarily showing polyols accumulation.